The Elm1 (ZmHy2) Gene of Maize Encodes a Phytochromobilin Synthase - Sawers, Ruairidh J.H. (American Society of Plant Biologists, 2004)
The light insensitive maize (Zea mays) mutant elongated mesocotyl1 (elm1) has previously been shown to be deficient in the synthesis of the phytochrome chromophore 3E-phytochromobilin (PΦB). To identify the Elm1 gene, a maize homolog of the Arabidopsis PΦB synthase gene AtHY2 was isolated and designated ZmHy2. ZmHy2 encodes a 297-amino acid protein of 34 kD that is 50% identical to AtHY2. ZmHY2 was predicted to be plastid localized and was targeted to chloroplasts following transient expression in tobacco (Nicotiana plumbaginifolia) leaves. Molecular mapping indicated that ZmHy2 is a single copy gene in maize that is genetically linked to the Elm1 locus. Sequence analysis revealed that the ZmHy2 gene of elm1 mutants contains a single G to A transition at the 3′ splice junction of intron III resulting in missplicing and premature translational termination. However, flexibility in the splicing machinery allowed a small pool of in-frame ZmHy2 transcripts to accumulate in elm1 plants. In addition, multiple ZmHy2 transcript forms accumulated in both wild-type and elm1 mutant plants. ZmHy2 splice variants were expressed in Escherichia coli and products examined for activity using a coupled apophytochrome assembly assay. Only full-length ZmHY2 (as defined by homology to AtHY2) was found to exhibit PΦB synthase activity. Thus, the elm1 mutant of maize is deficient in phytochrome response due to a lesion in a gene encoding phytochromobilin synthase that severely compromises the PΦB pool.